BaP exposure causes oocyte meiotic arrest and fertilization failure to weaken female fertility. Issue 1 (13th September 2017) - Zhang, Mianqun; Miao, Yilong; Chen, Qian; Cai, Meng; Dong, Wenkang; Dai, Xiaoxin; Lu, Yajuan; Zhou, Changyin; Cui, Zhaokang; Xiong, Bo
Abstract : Benzo[a]pyrene (BaP) is a ubiquitous environmental pollutant and carcinogen that is frequently found in particulate matter, with a diameter of ≤2.5 μm (PM2.5). It has been reported to interrupt the normal reproductive system, but the exact molecular basis has not been clearly defined. To understand the underlying mechanisms regarding how BaP exposure disrupts female fertility, we evaluated oocyte quality by assessing the critical regulators and events during oocyte meiotic maturation and fertilization. We found that BaP exposure compromised the mouse oocyte meiotic progression by disrupting normal spindle assembly, chromosome alignment, and kinetochore‐microtubule attachment, consequently leading to the generation of aneuploid eggs. In addition, BaP administration significantly decreased the fertilization rate of mouse eggs by reducing the number of sperm binding to the zona pellucida, which was consistent with the premature cleavage of N terminus of zona pellucida sperm‐binding protein 2 and precocious exocytosis of ovastacin. Furthermore, BaP exposure interfered with the gamete fusion process by perturbing the localization and protein level of Juno. Notably, we found that BaP exposure induced oxidative stress with an increased level of reactive oxygen species and apoptosis in oocytes and therebyled to the deterioration of critical regulators and events during oocyte meiotic progression and fertilization. Our data document that BaP exposure reduces female fertility via impairing oocyte maturation and fertilization ability induced by oxidative stress and early apoptosis in murine models.—Zhang, M., Miao, Y., Chen, Q., Cai, M., Dong, W., Dai, X., Lu, Y., Zhou, C., Cui, Z., Xiong, B. BaP exposure causes oocyte meiotic arrest and fertilization failure to weaken female fertility. FASEB J. 32, 342‐352 (2018). www.fasebj.org